2000
DOI: 10.1128/mcb.20.15.5454-5468.2000
|View full text |Cite
|
Sign up to set email alerts
|

BNIP3 and Genetic Control of Necrosis-Like Cell Death through the Mitochondrial Permeability Transition Pore

Abstract: Many apoptotic signaling pathways are directed to mitochondria, where they initiate the release of apoptogenic proteins and open the proposed mitochondrial permeability transition (PT) pore that ultimately results in the activation of the caspase proteases responsible for cell disassembly. BNIP3 (formerly NIP3) is a member of the Bcl-2 family that is expressed in mitochondria and induces apoptosis without a functional BH3 domain. We report that endogenous BNIP3 is loosely associated with mitochondrial membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
472
1
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 570 publications
(510 citation statements)
references
References 66 publications
34
472
1
3
Order By: Relevance
“…BNIP3-mediated atypical cell death has also been reported in other cell systems, where cells exhibited nuclear apoptotic change in the absence of Apaf-1, cytochrome c release and caspase activation [40,41]. We have also observed that cyanide can produce apoptosis in rat primary cortical cells in which BNIP3 released cytochrome c from mitochondria, followed by caspase-dependent apoptosis [18].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…BNIP3-mediated atypical cell death has also been reported in other cell systems, where cells exhibited nuclear apoptotic change in the absence of Apaf-1, cytochrome c release and caspase activation [40,41]. We have also observed that cyanide can produce apoptosis in rat primary cortical cells in which BNIP3 released cytochrome c from mitochondria, followed by caspase-dependent apoptosis [18].…”
Section: Discussionsupporting
confidence: 76%
“…Forced overexpression of BNIP3 in Mes 23.5 cells decreased ΔΨ m , which was prevented by CsA, an MPT inhibitor. Previous studies have shown that upon overexpression, BNIP3 integrates into the outer mitochondrial membrane with a special orientation of the N-terminus in the cytoplasm and Cterminus in the membrane [41]. After integration into the mitochondrial membrane, BNIP3 may interact with components of the MPT pore to induce rapid opening of the MPT pore to dissipate ΔΨm.…”
Section: Discussionmentioning
confidence: 99%
“…47 Overexpression of BNIP3 results in a caspaseindependent cell death with features of necrosis, including opening of the permeability transition pore, and evidence of mitochondrial autophagy. 48 Hspin is a transmembrane protein that is localized primarily in the mitochondria. Overexpression of HSpin (the human Spin homologue) also induces a caspase-independent cell death that involves mitochondrial autophagy and is inhibited by Bcl-2 and Bcl-xL.…”
Section: Inhibition Of Apoptosis Upstream Of the Mitochondria Preventmentioning
confidence: 99%
“…Forced expression of BNIP3 induces cell death characterised by localisation of the protein at the mitochondria, opening of the permeability transition pore, loss of membrane potential and production of reactive oxygen species (Regula et al, 2002;Vande Velde et al, 2000). This form of cell death is independent of cytochrome c release from mitochondria and caspase activation (Vande Velde et al, 2000).…”
mentioning
confidence: 99%
“…Forced expression of BNIP3 induces cell death characterised by localisation of the protein at the mitochondria, opening of the permeability transition pore, loss of membrane potential and production of reactive oxygen species (Regula et al, 2002;Vande Velde et al, 2000). This form of cell death is independent of cytochrome c release from mitochondria and caspase activation (Vande Velde et al, 2000). Expression of BNIP3, which is dramatically increased in response to hypoxia, is regulated in part by hypoxia-inducible factor-1 (HIF-1), a heterodimeric transcription factor comprised of an oxygenregulated a subunit (HIF-1a) and a stale nuclear factor (HIF-1b/ ARNT), and known to be a mediator of the hypoxic response (Semenza, 1999).…”
mentioning
confidence: 99%